Adnexal mass secondary to extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue (MALT lymphoma) with associated amyloid deposition. (14th November 2014) - Mehta, Neha; Schöder, Heiko; Chiu, April; Schoolmeester, John Kenneth; Portlock, Carol
Abstract : Systemic amyloid light chain amyloidosis (AL amyloidosis) is usually seen in association with a plasma cell disorder. Amyloid deposition associated with extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue (MALT lymphoma) is a rare phenomenon that is not typically associated with systemic AL amyloidosis. We describe the unusual case of a patient with an adnexal mass secondary to MALT lymphoma with associated amyloid deposition.